Perception and Practice: Investigating English Pronunciation Mastery Among Postgraduate Students - Atoriq Nurriza,; M. Misbahul Amri,; Nurenzia Yannuar, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Particularly for postgraduate students who specialize in English education, the acquisition of different and accurate pronunciation is an essential component of language proficiency, as it has a substantial influence on their academic achievement and future professional pursuits. Despite its significance, the mastery of pronunciation remains a difficult task because of the interplay of numerous factors and particular features of each student. This study investigates a comprehensive investigation regarding on postgraduate students’ perception in mastering English pronunciation. This study also aims to discover students’ practice in mastering English pronunciation. This study employs a descriptive-qualitative design. To collect the data, the instruments used observation, and a semi-structured interview. The participants in this study were six postgraduate students enrolled in an English education major at one of the universities in Malang. This study used convenience sampling to elicit the participants. The findings reveals that all postgraduate students face some factors that influences their English pronunciation. There are age, exposure, innate phonetic ability, attitude, and motivation. Each of these elements significantly influences the students' pronunciation abilities. Postgraduate students also employ various practices for mastering English pronunciation, including auditory perception, recollections, summary, and note-taking. Postgraduates use those practices to master English pronunciation